Risk taking Behavior and Mental Health among Physical Education Students - P. P , Shahanas; Kumar C. V., Harish (International Journal of Psychosocial Rehabilitation, 2020)
The study sought to determine the risk-taking behavior and mental health among physical education students. The sample consisted of 100 early adults (physical education students), 50 boys and 50 girls. Different statistical techniques were used to obtain the data. The method of selection was purposive sampling from different institutions in Kerala. Risk-taking behavior and mental health were calculated by using the questionnaires of risk-taking behavior and mental health profile. Statistical techniques such as t-tests, ANOVA, Scheffe’s post hoc tests, and the coefficient of correlation were used for the analysis of data. The findings illustrate that there is a relation between risk-taking behavior and mental health and that different variables affect the risk-taking behavior and mental health of physical education students.